Erythema dyschromicum perstans (ashy dermatosis) - opis przypadków - Jadwiga Roszkiewicz; Małgorzata Sokołowska-Wojdyło; Magdalena Lange; Magdalena Trzeciak (Termedia Publishing House, 2011)
Introduction. Erythema dyschromicum perstans (EDP) is an acquireddisease, rare in the Caucasian race, with characteristic greyish, ashycolouredskin lesions. The aetiology of the disease is unknown.Objective. To present 5 patients with EDP in relation to cases describedin the literature as: ashy dermatosis, lichen planus pigmentosus, idiopathiceruptive macular pigmentation.Case reports. We present 5 cases with chronic, macular grey pigmentationof the skin of the trunk and the limbs. In 2 cases simultaneousappearance of slightly erythematous reaction and itch of the skin wereobserved. The histopathological picture was similar in all cases. Themain features were: incontinentia of the pigment, slight inflammatory Początkoinfiltrates,and melanophages in the upper dermis. In 2 cases we observeddegeneration of the basal cell layer. The course of the diseases wasmild. Other laboratory tests were normal. In the majority of cases thecause of the disease was toxic.Conclusions. It seems that discrete differences in histopathological pictureand colouring of the lesions are not sufficient to differentiate EDPfrom ashy dermatosis, lichen planus pigmentosus and idiopathic eruptivemacular pigmentation. We believe that all these conditions are formsof the same disease.